Motorcycle Riders’ Perception of the Characteristics of Paratransit In Medan, Indonesia - Siahaan, Reynaldo; Sitindaon, Charles; Sitohang, Oloan (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2020)
In developing countries, the uncontrolled rise of private vehicle ownership, such as motorcycles, constitutes a great deal of air pollution in the city. While the motorcycle is quite convenient, public transport lacks many qualities, and for some cities, like Medan, they are limited to paratransit. This study aims to reach an understanding of motorcycle riders’ perception of the existing paratransit and its relation to their reasoning to choose the two-wheelers daily. We utilized a structured questionnaire and interviewed 456 daily-commuting riders to assess 13 service aspects of the existing paratransit and their primary reason for using a motorcycle. Our findings suggest that riders collectively agree that affordable fare, easy to find, and short walking distance are the best trait of the existing public transport in Medan. Meanwhile, travel time, time-availability, and hygienic issues are reported to be the most hindering aspects. This perspective is consistent with riders’ reasoning behind their mode choice, which is based primarily on time efficiency. This research highlights the comparison of riders’ need in commuting and their opinion about the existing paratransit. While it is yet interesting to learn how those aspects weigh in with each other, the result of this study still offers prudent recommendations in developing mode-shifting strategic policies to encourage more public transportation use in Medan city.